Functional Interest Advocacy in Modern Complex Litigation - Timothy Wilton (Washington University Law Quarterly, 1982)
This Article proposes a functional analysis of the interests affected by the lawsuit and suggests techniques for the individuals with those interests to become involved in the litigation and to advocate those interests to the judge before the decision is made. In every case, the court should consider whether and in what way individuals other than the parties may be affected. In cases in which absentees may be affected or in which the parties are complex legal entities composed of a number of individuals, the court should organize the interests into outcome positions for advocacy rather than assume that each party contains a unitary interest. The court should ensure that there is an advocate for each outcome position and that the individuals who support each position know who their advocate is and have a means for communicating with that advocate. In other words, the lawyers should represent positions rather than parties. In this way the litigation will involve all the affected individuals, and all will have their interests represented. The judge will have the information and arguments from all the points of view and thus will be better able to make a well-informed decision. Finally, the people who must carry out the remedial order will be more cooperative, because they will think the decision was reached fairly. In simple private litigation, the adversary process does this interest organization and involvement automatically. In modem complex public litigation, however, the adversary system does not work automatically. The judge must guide its workings to implement its policies. This Article first will explore in greater depth the nature and source of the problem, so as to alert judges to the situations in which they must modify the adversary system in order to obtain adequate representation of all affected interests. This Article then proposes a method of interest analysis, involvement, and advocacy, with several examples of how the method would work in the types of problems of interest representation most common in modem litigation.
Keywords: Complex litigation